The Central American Integration System (SICA) advances on the implementation of the CSA regional strategy for 2018-2030 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS led the technical component in the formulation process of the CSA regional strategy for SICA region, as a request from the Central-American-Agricultural-Council (CAC). CCAFS research outputs and expert support were key to develop a robust policy instrument that could continue in force despite a diversity of plausible future pathways considering climate change. The latter was achieved using CCAFS future scenarios methodology. The CSA-strategy has been able to attract USD$2million in terms of initiatives/projects for implementing CSA in the region.